Levantamento e diagnose das orquídeas (ORCHIDACEAE A. Juss.) de um fragmento de Floresta Ombrófila Mista do Centro-Oeste do Estado do Paraná - Costa, Alan Cezar (2018)
The Atlantic Forest is a biome with specificity of ecological interactions that has evolved over thousands of years, becoming one of the Hotspots with greater planet is richness of species, however very sensitive to human-made changes. Among the most fragile ecosystems in this biome, it is noticed the Floresta Ombrófila Mista (FOM) which is popularly known as Araucarias forest (Araucaria angustifolia Bertol. Kuntze). The present study of Orchidaceae species in fragments in this environment, revealed the expressive occurrence of species of this family, and even having homogeneous relief and small area, is able to harbor greater diversity than larger areas and with heterogeneous relief. Although there is a predominance of the two genus most common also to other Atlantic Forest phytophysiognomies, the fragment presented unusual and not yet unregistered orchids in FOM evidencing the local richness. The presence of 26 endemic species from Brazil, some still without confirmation in Brazil Flora 2020 for the Paraná State, indicates the ecological importance of this environment and its phytophysiognomies. Despite that some orchids species demonstrated participate of the species-specific relationships with exclusive forophytes of the FOM, and the degradation of this forest has made that some of the species found here appear on the Red List of Threatened Species as: "vulnerable," "near threatened” or “endangered”. Aiming to provide information to subsidize the conservation of species, and knowing the difficulty that normally there is in finding flowered orchids during the research period, the researchers were provided with ecological and phenological information of the species found, as well as a brief description of the species, with dichotomous keys based whenever possible on vegetative characters, with the view to facilitate the identification of the genera and species of their respective groups at any period of the year.